United Kingdom : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2000)
The paper addresses issues that arise in designing a framework for inflation targeting, with particular attention to features of the Bank of England's approach and experience. The comparison of welfare reform in the United Kingdom with similar efforts in other countries is discussed. The paper reviews the recent literature and empirical evidence on the main economic considerations influencing possible U.K. entry into the European Monetary Union (EMU). The U.K. labor market has undergone institutional and structural changes contributing to an increase in both aggregate and relative wage flexibility.